Myocardial signaling defects and impaired cardiac function of a human beta 2-adrenergic receptor polymorphism expressed in transgenic mice. - Turki, J (1996)
A threonine to isoleucine polymorphism at amino acid 164 in the fourth transmembrane spanning domain of the beta 2-adrenergic receptor (beta 2AR) is known to occur in the human population. The functional consequences of this polymorphism to catecholamine signaling in relevant cells or to end-organ responsiveness, however, are not known. To explore potential differences between the two receptors, site-directed mutagenesis was carried out to mimic the polymorphism. Transgenic FVB/N mice were then created overexpressing wild-type (wt) beta 2AR or the mutant Ile-164 receptor in a targeted manner in the heart using a murine alpha myosin heavy chain promoter. The functional properties of the two receptors were then assessed at the level of in vitro cardiac myocyte signaling and in vivo cardiac responses in intact animals. The expression levels of these receptors in the two lines chosen for study were approximately 1200 fmol/mg protein in cardiac membranes, which represents a approximately 45-fold increase in expression over endogenous beta AR. Myocyte membrane adenylyl cyclase activity in the basal state was significantly lower in the Ile-164 mice (19.5 +/- 2.7 pmol/min/mg) compared with wt beta 2AR mice (35.0 +/- 4.1 pmol/min/mg), as was the maximal isoproterenol-stimulated activity (49.8 +/- 7.8 versus 77.1 +/ 7.3 pmol/min/mg). In intact animals, resting heart rate (441 +/- 21 versus 534 +/- 17 bpm) and dP/dtmax (10,923 +/- 730 versus 15,308 +/- 471 mmHg/sec) were less in the Ile-164 mice as compared with wt beta 2AR mice. Similarly, the physiologic responses to infused isoproterenol were notably less in the mutant expressing mice. Indeed, these values, as well as other contractile parameters, were indistinguishable between Ile-164 mice and nontransgenic littermates. Taken together, these results demonstrate that the Ile-164 polymorphism is substantially dysfunctional in a relevant target tissue, as indicated by depressed receptor coupling to adenylyl cyclase in myocardial membranes and impaired receptor mediated cardiac function in vivo. Under normal homeostatic conditions or in circumstances where sympathetic responses are compromised due to diseased states, such as heart failure, this impairment may have important pathophysiologic consequences.